Analisis Faktor Keberhasilan Desa Adat Dayak Iban Sungai Utik dalam Memenangkan Equator Prize Tahun 2019 - Dwi Prasetyo; Suranto (Pencerah Publishing, 2021)
The research aims to analyze the factors that cause the Indigenous Dayak people of Iban Sungai Utik to maintain their living ecosystem (tembawang) which has implications for the awarding of equator prizes, identifying customary governance, as well as the dynamics that occur between the government and the indigenous peoples of Dayak Iban Sungai Utik in conservation issues in Kapuas Hulu Regency. This research uses descriptive qualitative research methods through a case study approach, with data obtained through observation, interviews, and documentation. Then data analysis is carried out with the stages of data reduction, interpretation, presentation of data, and also withdrawal of conclusions. The results showed that management patterns and community paradigms related to the existence of forests that became the basis of subsistence of local communities based on the perspective of community-based forest management. Through the four main variables of community-based forest management, researchers also explained the relationship and dynamics of the Dayak Iban Sungai Utik community with its nature, conservation strategies adopted by local communities in response to post-reform socio-political changes, and relations between countries and indigenous peoples in the governance policy of the Utik River region. The conclusion is that customary law regulated by the indigenous peoples of Dayak Iban Sungai Utik in the context of Utik River management becomes a key entintas in the sustainability of the Utik River ecosystem. This paid off with the award of the Equator Prize by the United Nations along with 22 other communities for their persistence in maintaining their living space.